2017
DOI: 10.2169/internalmedicine.56.7439
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tumor Thrombotic Microangiopathy Caused by a Parotid Tumor: Early Antemortem Diagnosis and Long-term Survival

Abstract: Pulmonary tumor thrombotic microangiopathy (PTTM) is a high-mortality disease that is difficult to diagnose clinically. Our patient was an 80-year-old woman who came to us due to symptoms of increasing dyspnea. A clinical evaluation showed that she had hypoxemia and pulmonary arterial hypertension without any abnormalities in the major pulmonary arteries, bronchi, or alveoli. A lung perfusion scan showed multiple wedge-shaped perfusion defects. Further examination revealed adenocarcinoma in her right parotid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…These are novel findings that support the diagnosis of this PTTM, as well as a deeper understanding of its morphology. While previous reports have also mentioned arteriolar involvement at various sizes, we observed a predominance of arterioles smaller than 150 μm in diameter. Based on this, four cases in the suspicious PTTM group were identified as not being belonging to this group, but were cases with incidental pulmonary tumour emboli coexistent with lymphangitic carcinomatosis causing respiratory symptoms.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…These are novel findings that support the diagnosis of this PTTM, as well as a deeper understanding of its morphology. While previous reports have also mentioned arteriolar involvement at various sizes, we observed a predominance of arterioles smaller than 150 μm in diameter. Based on this, four cases in the suspicious PTTM group were identified as not being belonging to this group, but were cases with incidental pulmonary tumour emboli coexistent with lymphangitic carcinomatosis causing respiratory symptoms.…”
Section: Discussioncontrasting
confidence: 82%
“…Although PTTM has been mainly discovered by autopsy, it is becoming increasingly well known by physicians . Several authors have reported on the efficacy of multimodal therapy, and, consequently, the importance of an antemortem diagnosis is growing in order to temper this agonising disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT findings for PTTM have ground glass centrilobular micronodules, thickening of the intra-and interlobular septa, and a tree-in-bud pattern, which may represent fibrocellular in- timal proliferation of the small pulmonary arteries, but may also be found in other lung diseases, such as infectious bronchiolitis [13,14] . In some previously reported cases, PTTM was suspected antemortem from the findings of an elevated right ventricular systolic pressure in echocardiography, no thrombi in CT pulmonary angiography or contrast-enhanced CT, and diffuse peripheral perfusion defects in pulmonary perfusion scintigraphy [15] . For a pathological diagnosis of PTTM, pulmonary wedge aspiration cytology [16,17] , transbronchial biopsy [8,18] , CT-guided needle biopsy [2] , and video-assisted thoracic surgery [10] have been reported to be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases are discovered at biopsy since there are no radiological features specific to PTTM, CT scan may be normal or shows dilated pulmonary arteries, wedge-shaped opacities peripherally, thickened interlobular septa or Tree-in-bud sign (centrilobular nodules with linear opacities) [27]. Perfusion studies may demonstrate defects and pathological studies with cytology and biopsy percutaneously or surgically may help in some cases [28]. Apart from supportive treatment and chemotherapy for the underlying malignancy, no specific treatments are available to withhold this fatal complication with most patients are dying shortly after diagnosis [29].…”
Section: Pulmonary Tumour Thrombotic Microangiopathymentioning
confidence: 99%